Pengaruh Dominasi Otak Kiri–Kanan terhadap Penguasaan Kaidah dan Mufrodat Bahasa Arab Santri MTs: Kajian Neurolinguistik: Hubungan Antara Dominansi Belahan Otak dan Penguasaan Tata Bahasa serta Kosakata Bahasa Arab di Kalangan Mahasiswa MTs: Sebuah Studi Neurolinguistik - Eka Sandri Yusuf; Damhuri; Wala Fahad bin Subait (ELOQUENCE : Journal of Foreign Language, 2026)
Background: Arabic language learning at the Madrasah Tsanawiyah (MTs) level demonstrates considerable variation in students' mastery of grammar and vocabulary. Some learners perform better in grammatical analysis, whereas others achieve stronger vocabulary mastery. From a neurolinguistic perspective, these variations may be associated with differences in brain hemisphere dominance during language processing. Purpose: This study aimed to examine the relationship between brain hemisphere dominance and the mastery of Arabic grammar and vocabulary among students at MTs Al-Islam Telaga Biru. Method: This study employed a quantitative correlational design involving 60 female students from Class IX-6 and Class IX-7 selected through total sampling. Data were collected using a 20-item brain hemisphere dominance questionnaire and achievement tests measuring Arabic grammar and vocabulary mastery. Data were analyzed using descriptive statistics and Pearson's product-moment correlation with IBM SPSS Statistics Version 29. Results and Discussion: Based on the questionnaire scores, 20 students were classified as left-brain dominant and 40 as right-brain dominant. Students classified as left-brain dominant tended to obtain higher grammar scores, whereas those classified as right-brain dominant tended to achieve higher vocabulary scores. Pearson's correlation analysis revealed a very strong negative relationship between brain dominance scores and grammar mastery (r = −0.927, p < 0.01) and a very strong positive relationship between brain dominance scores and vocabulary mastery (r = 0.963, p < 0.01). Conclusions and Implications: The findings indicate a significant relationship between brain hemisphere dominance and Arabic grammar and vocabulary mastery. These findings suggest that Arabic language teachers should consider students' hemispheric learning tendencies when designing differentiated instructional strategies that accommodate diverse learning characteristics.